(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Erectile Dysfunction (ED) describes the persistent inability to achieve or maintain a penile erection for adequate sexual performance. ED is thought to be a vascular disease affecting more than 70% of men with (Cardiovascular Disease) CVD and sharing a myriad of risk factors like hypertension, smoking, diabetes, obesity, ageing and the metabolic syndrome. Diabetes increases the risk of both ED and CVD with the latter being the leading cause of death. Endothelial dysfunction and its role in the development of atherosclerosis may be the common link between ED, CVD and diabetes. With the current epidemic of type 2 diabetes, diabetes related CVD will increase in tandem. Early identification of this risk group is therefore paramount. Evidence has shown that ED is an independent marker of increased CVD risk and heralds the onset of coronary artery disease, peripheral arterial disease and stroke thereby providing a window of opportunity for risk factor modification. In our paper we shall explore the correlation of ED and CVD with a view to formulation of intervention strategies. Chatt Maa Shi Hosp Med Coll J; Vol.18 (2); July 2019; Page 59-66